Actinomycetes isolated from medicinal plant rhizosphere soils: diversity and screening of antifungal compounds, indole-3-acetic acid and siderophore production - Khamna, Sutthinan; Yokota, Akira; Lumyong, Saisamorn (World journal of microbiology & biotechnology, 2009)
A total of 445 actinomycete isolates were obtained from 16 medicinal plant rhizosphere soils. Morphological and chemotaxonomic studies indicated that 89% of the isolates belonged to the genus Streptomyces, 11% were non-Streptomycetes: Actinomadura sp., Microbispora sp., Micromonospora sp., Nocardia sp, Nonomurea sp. and three isolates were unclassified. The highest number and diversity of actinomycetes were isolated from Curcuma mangga rhizosphere soil. Twenty-three Streptomyces isolates showed activity against at least one of the five phytopathogenic fungi: Alternaria brassicicola, Collectotrichum gloeosporioides, Fusarium oxysporum, Penicillium digitatum and Sclerotium rolfsii. Thirty-six actinomycete isolates showed abilities to produce indole-3-acetic acid (IAA) and 75 isolates produced siderophores on chrome azurol S (CAS) agar. Streptomyces CMU-PA101 and Streptomyces CMU-SK126 had high ability to produced antifungal compounds, IAA and siderophores.